Inovasi Es Krim Susu Sapi: Menyegarkan Pasar dan Mendorong Ekonomi Kreatif - Rachmawati, Putri; Zuhair, Aprizal Hakim; Meilani, Siti Nabilah; Rahmatulloh, Yusuf Irawan; Patimah, Ellisyia Nur; Marenka, Nofira Nabila; Fachrizal, Mochamad Aldi Raihan; Dwisari, Elvina; Aslam, Muzaki; Rachman, Abirama Ramadhan (Universitas Muhammadiyah Yogyakarta, 2025)
Boyong hamlet is one of the hamlet where most of the livelihoods are dairy farmers. Almost all residents in this dukuhan depend on their livelihood as livestock breeders. However, breeders in Padukuhan Boyong still face various challenges in their development efforts. One of them is selling pure milk directly to collectors with the shelf life of the milk being very short so that when it is not collected by the collector the pure milk will go stale. This service activity provides fresh ideas in the economic market in Padukuhan Boyong by changing pure milk into ice cream. The aim of this service activity is to increase the innovation of cow's milk farming products into ice cream so that it can stimulate the economy and create something new in the market in Padukuhan Boyong. This activity method uses Participatory Action which provides empowerment through observation, interviews, FGD, training, mentoring and evaluation. The result of this empowerment is training for cattle breeders in processing an interesting product, namely ice cream, as well as encouraging the economy through digitalization in website-based product marketing. The conclusion of this service activity is the innovation of cow's milk farming products into ice cream, to increase the sales value of pure milk, through the results of the training, almost all of the training participants, previously 10% of whom did not understand how to make cow's milk into ice cream, after the training, almost half of the participants understood the basic techniques for processing it into ice cream, reaching 85.7%, and the results of digitalization to boost the economy were creating a website https://www.boyongmilk.com so that it could expand the creative economy with marketing other than catalogs on WhatsApp